Synaptosomal bioenergetic defects are associated with cognitive impairment in a transgenic rat model of early Alzheimer's disease. Issue 1 (January 2017) - Martino Adami, Pamela V; Quijano, Celia; Magnani, Natalia; Galeano, Pablo; Evelson, Pablo; Cassina, Adriana; Do Carmo, Sonia; Leal, María C; Castaño, Eduardo M; Cuello, A Claudio; Morelli, Laura
Synaptic bioenergetic deficiencies may be associated with early Alzheimer's disease (AD). To explore this concept, we assessed pre-synaptic mitochondrial function in hemizygous (+/−)TgMcGill-R-Thy1-APP rats. The low burden of Aβ and the wide array of behavioral and cognitive impairments described in 6-month-old hemizygous TgMcGill-R-Thy1-APP rats (Tg(+/−)) support their use to investigate synaptic bioenergetics deficiencies described in subjects with early Alzheimer's disease (AD). In this report, we show that pre-synaptic mitochondria from Tg(+/−) rats evidence a decreased respiratory control ratio and spare respiratory capacity associated with deficits in complex I enzymatic activity. Cognitive impairments were prevented and bioenergetic deficits partially reversed when Tg(+/−) rats were fed a nutritionally complete diet from weaning to 6-month-old supplemented with pyrroloquinoline quinone, a mitochondrial biogenesis stimulator with antioxidant and neuroprotective effects. These results provide evidence that, as described in AD brain and not proven in Tg mice models with AD-like phenotype, the mitochondrial bioenergetic capacity of synaptosomes is not conserved in the Tg(+/−) rats. This animal model may be suitable for understanding the basic biochemical mechanisms involved in early AD.